The Essential Needs in Developing Genre-Based Pedagogy Teaching Materials for Essay Writing - Eka Yulianti; Johanes Sapri; Didi Yulistio; Elce Purwandari (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
Essay writing is an important academic skill in higher education because it requires not only language proficiency but also critical and analytical thinking. However, existing teaching materials often do not fully support students in developing these skills. This study aims to analyze students’ needs for genre-based essay writing teaching materials in the Indonesian Language Education program. The research used a descriptive quantitative approach involving 150 undergraduate students from UIN Fatmawati Sukarno Bengkulu and IAIN Curup. Data were collected using a 15-item questionnaire on a five-point Likert scale, covering content, language, structure, and media aspects. The results showed a needs score of 60.16%, categorized as “needed,” indicating that current materials are still insufficient. Students need clearer explanations, structured writing steps, genre examples, simple academic language, and supportive visual media. All questionnaire items were valid and reliable (Cronbach’s Alpha = 0.971). Therefore, systematic, student-centered teaching materials need to be developed to support essay writing instruction better.